Spectral properties of Er-doped yttrium aluminum garnet crystals grown by modified horizontal directional crystallization method - Nizhankovskyi, S.V.; Kozlovskyi, A.A.; Kovalenko, N.O.; Kryvonogov, S.I.; Siryk, Yu.V. (Functional Materials, 2018)
For the first time Er³⁺-doped yttrium aluminum garnet single crystals were grown by modified horizontal directional crystallization method in the reducing atmosphere Ar+(CO, H₂). The absorption and photoluminescence spectra of the grown crystals were measured. The absorption spectra consisted of the bands corresponding to the optical transitions between the ground and the excited states of Er³⁺ ions and the bands caused by intrinsic defects and the impurity ions Ti³⁺. Post-growth annealing in an oxidizing atmosphere reduced or eliminated these absorption bands. The IR photoluminescence spectra consisted of several emission peaks in 1450-1700 nm region. The up-conversion photoluminescence lines in the UV region at 382 nm excitation were detected. A model is proposed in which the absorption by the excited state is considered to be the main up-conversion mechanism.